2018
DOI: 10.5937/ekonomika1801037i
|View full text |Cite
|
Sign up to set email alerts
|

Implications of modern technology development for the tourism sector of the Republic of Serbia

Abstract: Tourism is often defined as an economic sector that deals with innovation and production of tourism products and services. It is a very complex economic sector, since tourism products and stakeholders are constantly changing due to changing external forces. Therefore, development and progress of information and communication technology have had an enormous impact on tourism as well as on other sectors of the economy associated with it. Over the years, the use of modern technology in tourism has been expanded t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 14 publications
1
7
0
3
Order By: Relevance
“…Methodologically closer to our study is that of Nonthapot and Watchalaanun (2015) who validated a causal relationship between tourist development and telecommunication investment in Thailand using time series data over the period 1983-2013. Tichaawa (2017) also observed that Information and Communication structures were associated with increased competitiveness for a cross section of tourism related business in South Africa, while Ilic and Nicolic (2018), also found a moderate positive and significant relationship between the degree of contribution of ICT readiness pillar and the competitiveness of the tourism sector in the Republic of Serbia using correlation analysis.…”
Section: Estimation Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Methodologically closer to our study is that of Nonthapot and Watchalaanun (2015) who validated a causal relationship between tourist development and telecommunication investment in Thailand using time series data over the period 1983-2013. Tichaawa (2017) also observed that Information and Communication structures were associated with increased competitiveness for a cross section of tourism related business in South Africa, while Ilic and Nicolic (2018), also found a moderate positive and significant relationship between the degree of contribution of ICT readiness pillar and the competitiveness of the tourism sector in the Republic of Serbia using correlation analysis.…”
Section: Estimation Resultsmentioning
confidence: 97%
“…The authors confirmed that the number of tourist arrivals and telecommunication investment have a long-term relationship. Other related studies have only indirectly linked ICT to tourism through channels related to competitiveness (Buhalis, 1998,2003; Namasivayam et al , 2000; Buhalis and O’Connor (2005), Mihalič and Buhalis, 2013; Tichaawa, 2017; Kim and Kim, 2017, Ilic and Nicolic (2018), productivity (Aramendia-Muneta and Ollo-Lopez, 2013; Buhalis, 2003; Buhalis and Molinaroli, 2003; Chandler and Munday, 2011), operation cost reduction (Inkpen, 1998; Sheldon, 1997; Bojnec and Kribel, 2004; Buhalis and Kaldis, 2008; Tichaawa, 2017) and tourism promotion (Buhalis, 1998; Luo et al , 2004, Buhalis and Law, 2008; Romanazzi et al , 2011) among others.…”
Section: Related Literaturementioning
confidence: 99%
“…Teknologi informasi dan komunikasi (TIK) memiliki pengaruh positif yang signifikan terhadap pertumbuhan dan perkembangan pariwisata (Ilić & Nikolić, 2018;TFAILY, 2018;Tsaurai & Chimbo, 2019). Perkembangan TIK telah terbukti mendukung peningkatan kualitas sektor pariwisata di Indonesia, di antaranya melalui platform E-Commerce yang turut membantu pelaku usaha dan pemerintah untuk meningkatkan kinerja sektor pariwisata di Indonesia baik dari sisi teknologi maupun melalui edukasi bagi para pemangku kepentingan.…”
Section: Kelima Pro Technology (Penggunaan Teknologi)unclassified
“…The Internet has changed the tourists' behavior regarding travel reservations (Mills & Law, 2004;Ilić & Nikolić, 2018). The main reason for this change is the fact that the Internet offers opportunity for easy and direct interaction and exchange of information between suppliers, on the one hand (such as hotels, airlines, car rentals), and tourists, on the other, thus bypassing traditional travel agencies (Werthner & Klein, 1999 Klahn, 2015), and to access this information 24/7 ).…”
Section: Role Of the Internet In Tourismmentioning
confidence: 99%